2009
DOI: 10.1161/circresaha.108.176008
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of a Retinal Aldosterone System and the Protective Effects of Mineralocorticoid Receptor Antagonism on Retinal Vascular Pathology

Abstract: Blockade of the renin-angiotensin-aldosterone system (RAAS) is being evaluated as a treatment for diabetic retinopathy; however, whether the mineralocorticoid receptor (MR) and aldosterone influence retinal vascular pathology is unknown. We examined the effect of MR antagonism on pathological angiogenesis in rats with oxygen-induced retinopathy (OIR). To determine the mechanisms by which the MR and aldosterone may influence retinal angiogenesis; inflammation and glucose-6-phosphate dehydrogenase (G6PD) were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
152
2
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(166 citation statements)
references
References 39 publications
7
152
2
5
Order By: Relevance
“…121 Of great interest, it has recently been suggested that, similar to what has been described in the heart, brain and vasculature, 122 the eye has a dynamic aldosterone-mineralocorticoid receptor system that has an important pathophysiological role in the development of retinal pathology. Wilkinson-Berka et al 123 , using a rat model of oxygen-induced retinopathy (OIR) that has features of premature retinopathy in humans with neovascularization, have shown that mineralocorticoid receptor antagonism with spironolactone improves retinal angiogenesis by attenuating leukostasis and decreasing proinflamatory responses. These beneficial effects of spironolactone were attributed, at least in part, to a reduction in oxidative stress.…”
Section: Role Of Renin-ang Aldosterone System With Emphasis On Aldostmentioning
confidence: 99%
See 1 more Smart Citation
“…121 Of great interest, it has recently been suggested that, similar to what has been described in the heart, brain and vasculature, 122 the eye has a dynamic aldosterone-mineralocorticoid receptor system that has an important pathophysiological role in the development of retinal pathology. Wilkinson-Berka et al 123 , using a rat model of oxygen-induced retinopathy (OIR) that has features of premature retinopathy in humans with neovascularization, have shown that mineralocorticoid receptor antagonism with spironolactone improves retinal angiogenesis by attenuating leukostasis and decreasing proinflamatory responses. These beneficial effects of spironolactone were attributed, at least in part, to a reduction in oxidative stress.…”
Section: Role Of Renin-ang Aldosterone System With Emphasis On Aldostmentioning
confidence: 99%
“…These beneficial effects of spironolactone were attributed, at least in part, to a reduction in oxidative stress. Further observations in cultured retinal cells and in vivo in OIR suggested that reduction in oxidative stress may be secondary to a decrease in G6PD and retinal NADPH oxidase subunit Nox4 (Wilkinson-Berka et al 123 ). Together, these observations suggest that mineralocorticoid receptor antagonism may improve diabetic nephropathy and retinopathy by restoring G6PD activity and consequently reducing oxidative stress and inflammation.…”
Section: Role Of Renin-ang Aldosterone System With Emphasis On Aldostmentioning
confidence: 99%
“…From PD0 to PD11, pups were exposed to 80% oxygen (wt/wt) for 22 h/day and room air for 2 h/day, a process that suppresses retinal physiological angiogenesis [7,9]. On PD12, pups were placed in room air until PD18, which induces an increase in angiogenic and inflammatory factors, and neoangiogenesis [7,9].…”
Section: Animals Procedures Complied With the Alfred Medicalmentioning
confidence: 99%
“…Separate quantification was performed for central retina (0 to 1,666±166 μm from the optic disc), mid retina (1,667 to 3,050±154 μm) and peripheral retina (3, Neoangiogenesis in OIR Eyes were processed into paraffin, serially sectioned at 3 μm, and blood vessel profiles (BVPs) quantified in four non-overlapping fields of retina/section, with six sections/retina at least 60 μm apart evaluated per rat [9]. A BVP was defined as an endothelial cell or a blood vessel with a lumen.…”
Section: Animals Procedures Complied With the Alfred Medicalmentioning
confidence: 99%
See 1 more Smart Citation